(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
European Union’s (EU) enlargement policy is, for at least half a decade, facing a reality that, with quite some benevolence, could be defined as an orientation crisis, accompanied with a substantial lack of clarity and precision. The fact that, during the second half of 2019, both North Macedonia (NM) and Albania (AL) have not achieved the status of candidate countries was only a symptom – unfortunately not devoid of still unforeseeable internal political and economic consequences – of undeniable and profound discord between the EU member states over the future of the Union’s enlargement policy. When it comes to the two countries of the Western Balkans – Serbia (SR) and Montenegro (MN) – that are already in the process of membership negotiation, their relatively poor progress in 2019 – with either no further chapters provisionally closed (MN) or with only one chapter opened (SR) – only confirms the initial assessment about the fundamental crisis of this important EU policy. On the basis of scarce and mostly underdeveloped elements of the new enlargement methodology presented by the Commission in February 2020, this paper – using content analysis and scrutiny of negotiation-related polices of candidate countries – seeks to go beyond questions of conditionality and benchmarks, in order to examine some major consequences that this potentially new enlargement strategy could have. In spite of the fact that the focus of the analysis is put on some major changes the reorientation of this policy would entail, the author also examines (and, to some extent, predicts) what are the potential benefits and/or threats the new methodology could bring to both candidates and the EU itself. Without any pretention to provide final answers and apodictic conclusions, this paper proposes some elements of fine-tuning, in order to better define a potential change that encompasses the following three controversial elements: the wish for an encouragement, the reality of the fatigue and the threat of a dead end.